2021
DOI: 10.32771/inajog.v9i1.1397
|View full text |Cite
|
Sign up to set email alerts
|

Increased Levels of Umbilical Cord Blood Interleukin-6 (IL-6) and Serum C-Reactive Protein (CRP) in Premature Infants of Vitamin D Deficient Mothers

Abstract: Objective: Increased levels of inflammatory factors in newborns are often associated with lower maternal vitamin D levels. This study aimed to find out the relationship between maternal and umbilical cord vitamin D serum levels on umbilical cord Interleukin-6 (IL-6) and serum C-Reactive Protein (CRP) levels in premature infants.Methods: The study was an observational analytic, cross-sectional design in mothers who underwent preterm birth at 28-34 weeks' gestation due to premature rupture of membranes (PROM) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…Escalation in vitamin D levels will modulate and reduce TLR 2, TLR 4, and TLR 9 levels, thereby reducing IL-6 secretion as a marker of inflammation in circulation [8]. In line with the research by Lisnawati, Marianna, and Rohsiswatmo [4] it was stated that vitamin D plays a role in inhibiting the production of IL-6 cytokines and found a tendency for cord IL-6 levels and serum C-reactive protein (CRP) babies to be higher in the group of mothers who are deficient vitamin D.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Escalation in vitamin D levels will modulate and reduce TLR 2, TLR 4, and TLR 9 levels, thereby reducing IL-6 secretion as a marker of inflammation in circulation [8]. In line with the research by Lisnawati, Marianna, and Rohsiswatmo [4] it was stated that vitamin D plays a role in inhibiting the production of IL-6 cytokines and found a tendency for cord IL-6 levels and serum C-reactive protein (CRP) babies to be higher in the group of mothers who are deficient vitamin D.…”
Section: Introductionsupporting
confidence: 62%
“…Another study in healthy women aged 25 to 82 years reported that there appeared to be a slight trend toward an inverse relationship between serum 25(OH)D and IL-6 levels (p = 0.0909). These results indicate that the higher the mother's vitamin D level, the lower the expected level of IL-6 and CRP [4].…”
Section: Introductionmentioning
confidence: 84%
“…Rosendahl examined cord blood of 939 healthy term infants [ 20 ]. One study applied in pregnant women with preterm delivery and their infants cord blood [ 23 ]. Perichart-Perera et al examined the biomarkers of women with SGA fetus [ 24 ].…”
Section: Resultsmentioning
confidence: 99%